2018
DOI: 10.1002/ncp.10211
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Support in Adult Patients Receiving Extracorporeal Membrane Oxygenation

Abstract: The use of extracorporeal membrane oxygenation (ECMO) for both severe respiratory and cardiac failure is increasing. Because these patients are some of the sickest in the intensive care unit, a multidisciplinary approach to their treatment, including appropriate nutrition therapy, is warranted. Currently, limited data exist on the optimal timing, type, and amount of nutrition to be provided. This review focuses on describing the current nutrition practices in patients receiving ECMO, details research that is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 41 publications
1
30
0
15
Order By: Relevance
“…Early observational data from Ridley et al found bowel ischemia in 4.5% of 107 patients on ECMO receiving EN 33 . Other observational data show safety and tolerability of gastric EN delivery during ECMO 34 . Extrapolating from observational data from the H1N1 pandemic, most patients tolerated early EN within 24 hours of initiating ECMO.…”
Section: Recommendation 8: Nutrition Therapy During Ecmomentioning
confidence: 94%
“…Early observational data from Ridley et al found bowel ischemia in 4.5% of 107 patients on ECMO receiving EN 33 . Other observational data show safety and tolerability of gastric EN delivery during ECMO 34 . Extrapolating from observational data from the H1N1 pandemic, most patients tolerated early EN within 24 hours of initiating ECMO.…”
Section: Recommendation 8: Nutrition Therapy During Ecmomentioning
confidence: 94%
“…Data from several observational trials and a review article support the safety and tolerability of EN delivery during ECMO. 22 Large database studies on prospectively collected data of several thousand patients report that early EN resulted in decreased mortality, with no significant increase in episodes of ischemic bowel. 23,24 Thus, early EN may be initiated during use of ECMO, starting at trophic doses, with slow advancement over the first week of critical illness in patients with COVID-19.…”
Section: Nutrition Therapy During Ecmomentioning
confidence: 99%
“…Дані одного з досліджень свідчать про виявлення ішемії кишечника у 4,5% із 107 пацієнтів під час ЕКМО, які отримували ЕХ [33]. Інші дані літератури спостережень показують безпеку та переносимість проведення шлункового ЕХ під час ЕКМО [34].…”
Section: комбіноване (ентеральне плюс парентеральне харчування)unclassified